Effect of high purity molybdenum oxide(vi) on crystal growth and OLED technology. Issue 47 (23rd November 2021) - Khomyakov, Andrew; Sukhanova, Ekaterina; Mozhevitina, Elena; Zykova, Marina; Barkanov, Artem; Avetisov, Roman; Yurkin, Alexander; Subbotin, Kirill; Lis, Olga; Avetissov, Igor
Abstract : The strong influence of MoO3 chemical purity from 99.99 wt% to 99.999 wt% on lithium triborate (LBO) and NaLa(MoO4 )2 crystal growth as well as on OLED technologies has been demonstrated. Abstract : The strong influence of MoO3 chemical purity from 99.99 wt% to 99.999 wt% on lithium triborate (LBO) and NaLa(MoO4 )2 crystal growth as well as on OLED technologies has been demonstrated. The method of purification of molybdenum trioxide by vacuum sublimation under a controlled partial pressure of oxygen and chemical bonding of residual tungsten has been developed. Numerical simulation of the processing technique allowed the sublimation conditions to be specified and the parameters to be obtained, which defined the optimal yield of the condensed phase. The experimental optimization of the parameters made it possible to purify crystalline α-MoO3 at least up to 99.9993 wt% when 65 elements were detected by inductively coupled plasma mass-spectrometry.